Internalisasi Nilai-Nilai Sosial dalam Pembelajaran Pendidikan Agama Islam Sebagai Strategi Pembentukan Karakter Humanis di Era 5.0 - Dwi Adhi Widodo; Syaiful Hadi; Misbahun Nidhom (Al Mabhats : Jurnal Penelitian Sosial Agama, 2025)
The emergence of Society 5.0 represents a paradigm shift that integrates technology deeply into daily life while posing challenges such as social character degradation and digital individualism. This study qualitatively examines the strategic role of Islamic Religious Education (PAI) in fostering humanistic character and spirituality among learners in response to these changes. Through systematic literature review with descriptive-analytical design, findings reveal that digital-humanistic pedagogy, which positively integrates technology with ethical values, effectively internalizes social values in PAI. The implementation of blended learning and the "Kurikulum Merdeka" curriculum facilitates the transformation of abstract values into concrete social actions via project-based learning. Moreover, this research reconceptualizes PAI educators as mediators of digital ethics ("uswah hasanah digital"), transcending their traditional role as knowledge transmitters. In conclusion, adaptive and contextualized PAI serves as a crucial moral foundation in shaping devout individuals who are also responsible digital citizens. This underscores the importance of synergy between technology and value-based education to preserve humanity amid modernization pressures.